Monitoring Shallow Soil Water Content Under Natural Field Conditions Using the Early‐Time GPR Signal Technique. Issue 4 (1st July 2013) - Ferrara, C.; Barone, P.M.; Steelman, C. M.; Pettinelli, E.; Endres, A.L.
Abstract : It has been recently demonstrated that the early‐time portion of the ground‐penetrating radar (GPR) signal, consisting of the direct air and ground wave events, is dependent on the shallow subsurface bulk electromagnetic properties of the material; these properties are strongly controlled by the water content in this material. While several controlled experiments have been conducted to study the effects of water content variations on the antenna–material coupling, they considered a limited range of moisture variations and soil textures. Furthermore, those previous experiments did not consider highly dynamic shallow moisture responses that would be encountered under natural field conditions. For these reasons, general acceptance of this method requires that it be tested in real‐life applications. Our paper evaluates the early‐time GPR technique under natural field conditions where surface roughness, lithology, lateral heterogeneities, vegetation and water content dynamics are not controlled. We assess the capacity of the early‐time amplitude technique over the complete annual cycle of soil moisture conditions at three textural sites. To evaluate the sensitivity of the early‐time amplitudes to subsurface water content variations, we compare the early‐time results acquired using the enveloped amplitude of the first part of GPR signals with the bulk dielectric permittivity obtained from concurrently collected common‐midpoint direct ground wave velocity and gravimetric water content measurements. Our results demonstrate that the early‐time method can yield near‐surface permittivity information that is consistent with that obtained from direct ground wave velocity measurements, and accurate predictions of shallow soil moisture conditions.